EsrC, an envelope stress‐regulated repressor of the mexCD‐oprJ multidrug efflux operon in Pseudomonas aeruginosa. (22nd September 2014) - Purssell, Andrew; Fruci, Michael; Mikalauskas, Alaya; Gilmour, Christie; Poole, Keith
Summary mexCD ‐ oprJ is an envelope stress‐inducible multidrug efflux operon of Pseudomonas aeruginosa. A gene encoding a homologue of the NfxB repressor of this operon, PA4596, occurs downstream of oprJ and was proposed as a second repressor of this efflux operon. Inactivation of this gene had no impact on mexCD‐oprJ expression in cells not exposed to envelope stress although its loss under envelope stress conditions yielded a > 10‐fold increase in mexCD‐oprJ expression. Consistent with PA4596 functioning as a mexCD‐oprJ repressor, the purified protein was able to bind to a DNA fragment carrying the mexCD‐oprJ promoter region. Expression of PA4596 was induced under conditions of envelope stress dependent on the AlgU envelope stress sigma factor, consistent with PA4596 operating under envelope stress conditions where it possibly serves to moderate envelope stress‐inducible mexCD‐oprJ expression. nfxB mutants showed elevated PA4596 expression and purified NfxB bound to DNA encompassing the PA4596 upstream region, an indication that NfxB functions as a repressor of PA4596 expression. Elimination of PA4596 in P. aeruginosa lacking nfxB and hyperexpressing mexCD‐oprJ had no additional impact on mexCD‐oprJ expression, regardless of the presence of envelope stress, suggesting that PA4596 repressor activity may be dependent on NfxB. This envelope stress‐regulated repressor of mexCD‐oprJ has been renamed esrC.